State and Local Government and Politics Prospects for Sustainability - Simon, Christopher A.; Steel, Brent S.; Lovrich, Nicholas P. (Open textbook library., 2018)
Our book represents a unique opportunity for three generations of scholars to reflect upon and collectively consider their decades’ long research, and the meaning of that research to both the broader society and to students of contemporary politics. Nicholas Lovrich served as a graduate school mentor to Brent Steel, and Brent in turn mentored Christopher A. Simon as an undergraduate and guided him to study with Lovrich. Steel and Lovrich have collaborated on research for over 30 years, while Simon has frequently collaborated with Steel and Lovrich for nearly 20 years.